Study of Characteristics and Management of Drainage Problems in Ubud District - Irma Suryanti; Putu Indah Dianti Putri (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Ubud District is one of the tourism areas in Bali which is growing very rapidly. Ubud District has problems related to inundation and flooding which often occur during the rainy season. The drainage canals cannot accommodate the peak flood discharge. Because the capacity of the channel is insufficient, besides the influence of sediment and garbage, water overflows through the freeboard of the channel. This study aims to determine the characteristics of inundation and drainage in Ubud District. Primary and secondary data are used in this study which will then be used in data analysis. The analytical method used are field survey, identification of inundation and flood locations, inventory of existing drainage system, hydrology and hydraulics analysis, and drainage network planning. The result is 27 inundation locations were found in Ubud District. The inundation locations included 5 points in Lodtunduh Village, 3 points in Mas Village, 2 points in Peliatan Village, 5 points in Petulu Village, 2 points in Sayan Village, and 10 points in Ubud Village. The duration of the inundation that occurs is a minimum of 15 minutes and a maximum of 360 minutes. The height of the inundation that occurs is 12 – 50 cm with an inundation area of 0.032 – 4.67 ha and an inundation length of 12 – 2.309 m. The frequency of inundation is 3 to 10 times per year. Parameters for determining priority for drainage management based on priority scale are determined based on the characteristic parameters of inundation, economic losses, social disturbances and government facilities, transportation disturbances, and losses in residential areas. The recommendations given include normalizing the existing canal with river stone pairs of the required size that are more adequate to accommodate water discharge, especially during rains; making diversion channel with precast box culvert with the required size; and construction of new channels equipped with inlet drains per segment as entry points for inundation on the roads into the drainage channels.